Supporting social inclusion for students with autism spectrum disorders insights from research and practice - Little, Catherine A. (Routledge, 2017)
"Drawing together contributions from experts at the forefront of research in the field, Supporting Social Inclusion for Students with Autism Spectrum Disorders demonstrates that social inclusion is a defining feature of successful education of students with a spectrum disorder.Divided into three parts, this book begins by proposing a contemporary and operational definition of social inclusion that will help facilitate active engagement by all stakeholders involved in supporting social inclusion within educational settings."--Provided by publisher.